Geopolymer lightweight bricks manufactured from fly ash and foaming agent - Wan Ibrahim, Wan Mastura (American Institute of Physics, 2017)
This paper deals with the development of lightweight geopolymer bricks by using foaming agent and fly ash. The mix parameters analysed through a laboratory experiment with fix ratio of sodium silicate/sodium hydroxide solution mass ratio 2.5, fly ash/alkaline activator solution mass ratio 2.0, foaming agent/paste mass ratio 1:2 and molarity of sodium hydroxide solution used was 12M. Different curing temperature (Room Temperature, 60, 80) and foaming agent/water mass ratio (1:10 and 1:20) were studied. Compressive strength, density analysis, and water absorption has been investigated. The results show that the foamed geopolymer bricks with a lower foam/water mass ratio (1:10)and high curing temperature (80°C) leading to a better properties. Mixtures with a low density of around 1420 kg/m3 and a compressive strength of around 10 MPa were achieved.